Tools for fundamental analysis functions of TCR repertoires: a systematic comparison. (18th October 2019) - Zhang, Yanfang; Yang, Xiujia; Zhang, Yanxia; Zhang, Yan; Wang, Minhui; Ou, Jin Xia; Zhu, Yan; Zeng, Huikun; Wu, Jiaqi; Lan, Chunhong; Zhou, Hong-Wei; Yang, Wei; et al.
Abstract: The full set of T cell receptors (TCRs) in an individual is known as his or her TCR repertoire. Defining TCR repertoires under physiological conditions and in response to a disease or vaccine may lead to a better understanding of adaptive immunity and thus has great biological and clinical value. In the past decade, several high-throughput sequencing-based tools have been developed to assign TCRs to germline genes and to extract complementarity-determining region 3 (CDR3) sequences using different algorithms. Although these tools claim to be able to perform the full range of fundamental TCR repertoire analyses, there is no clear consensus of which tool is best suited to particular projects. Here, we present a systematic analysis of 12 available TCR repertoire analysis tools using simulated data, with an emphasis on fundamental analysis functions. Our results shed light on the detailed functions of TCR repertoire analysis tools and may therefore help researchers in the field to choose the right tools for their particular experimental design.